Global Inquiry Reveals PBL's Impact on Junior High Ecoliteracy: Global Inquiry Mengungkap Dampak PBL terhadap Ekoliterasi Sekolah Menengah Pertama - Amelia, Dita; Wulandari, Fitria Eka (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of Problem-Based Learning (PBL) on the ecoliteracy abilities of grade VII junior high school students compared to conventional lecture-based instruction. Conducted at SMP Muhammadiyah 6 Krian, the quasi-experimental research involved 40 students divided into experimental and control groups. Pre-test and post-test assessments using ecoliteracy indicators were conducted. Results from T-tests showed no significant difference in ecoliteracy abilities between the two groups (experimental group: p = 0.090, control group: p = 0.270), suggesting that PBL did not significantly improve ecoliteracy skills among grade VII students. These findings underscore the need for further exploration of instructional methods to enhance ecoliteracy in junior high school settings. Highlight: PBL's Effect on Ecoliteracy: Assessing PBL's impact on junior high ecoliteracy. Quasi-Experimental Design: Non-equivalent control group method in research design. Call for Further Research: Identifying effective environmental education strategies. Keyword: Problem-Based Learning, Ecoliteracy, Junior High School, Quasi-Experimental Research, Environmental Education